Psychological Mediators of the Association Between Childhood Emotional Abuse and Depression: A Systematic Review - Li, Elizabeth Tianyu; Luyten, Patrick; Midgley, Nick (Frontiers in Psychiatry, 2020)
Background: A number of existing meta-analyses and narrative reviews have already addressed the relation between childhood adversity and depression, yet none of them has examined the specific link between emotional abuse and depression highlighted by previous research. It is no longer appropriate to regard childhood maltreatment as a unitary concept when considering its effects on subsequent depression; instead, subtypes of childhood maltreatment need to be scrutinized separately. This review addresses this significant gap by critically evaluating empirical studies examining psychological mediators of the relationship between childhood emotional abuse and subsequent depression. Methods: A systematic search of nine electronic databases was conducted to identify eligible studies published in English between January 1980 and January 2020. Given the heterogeneous outcomes of eligible studies and the inconsistent reporting of indirect effects, a narrative synthesis, rather than a quantitative meta-analysis, was conducted. An appraisal of methodological quality was also included. Results: We identified 34 papers, comprising 18,529 adults and 3,434 adolescents, including 888 clinical participants. Our synthesis suggests that studies on mediators in the emotional abuse–depression link have focused on five clusters of intervening variables: early maladaptive schemas, cognitive-personality variables, emotion dysregulation, interpersonal styles, and stressful negative events. Only 11 studies identified the unique contribution of emotional abuse to depression by controlling for other forms of childhood maltreatment. Conclusions: Our findings support several routes with relative consistency (e.g., early maladaptive schemas, hopelessness, negative cognitive styles, brooding rumination, overall emotion dysregulation). Because psychological mediators function as a complex interrelated system, controlling for the interrelation between them is important. The evidence for the purported mediating role of the factors identified in this review should be considered with caution given the relative dearth of large-scale, adequately powered longitudinal studies. This review proposes a comprehensive multilevel theoretical framework as a basis for future research.